If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(c + 6) = -2(x + -4) Reorder the terms: 2(6 + c) = -2(x + -4) (6 * 2 + c * 2) = -2(x + -4) (12 + 2c) = -2(x + -4) Reorder the terms: 12 + 2c = -2(-4 + x) 12 + 2c = (-4 * -2 + x * -2) 12 + 2c = (8 + -2x) Solving 12 + 2c = 8 + -2x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2c = 8 + -12 + -2x Combine like terms: 12 + -12 = 0 0 + 2c = 8 + -12 + -2x 2c = 8 + -12 + -2x Combine like terms: 8 + -12 = -4 2c = -4 + -2x Divide each side by '2'. c = -2 + -1x Simplifying c = -2 + -1x
| 30-2x=6x+6 | | 3+9=-3(8x-4) | | 1K/3-4k/3= | | 3b-2(-5b+3)=12-5b | | 3b-2(5b+3)=12-5b | | 28x+4y=8 | | K/3-4k/3= | | 19x+11y=20900 | | 20=2(6)-8 | | -6(5k+4)=-114 | | 8.92x/133.8=(7.17)(35.85) | | 2x-8=2x-8 | | 36=3y-15 | | 6x^5/4x | | 2.5x^2=3x | | -16-3x=5-6x | | .11x+.05(7500-x)=675 | | 2+3(6)= | | 5ln(5x+2)=22 | | 2=m^2-7 | | 5×5/6 | | Y=0.002x+0.000 | | -4x+3=-5x-4 | | 3(11x-7)=13+25 | | 3x/2-x/3=5(x-4)/6 | | 64x+44=-20 | | 64x+4=-20 | | (x-10)/75=8 | | -1/2(1-5p)=2/3(p-7)-5 | | 0=x^2-6.6x+8 | | 96+x=7x+36 | | 5ax+7a-10x-14= |